Risk Factors for Brain Injury in Newborns Treated with Extracorporeal Membrane Oxygenation - Melbourne, Launice; Wien, Michael A.; Whitehead, Matthew T.; Ridore, Michelande; Wang, Yunfei; Short, Billie L.; Bulas, Dorothy; Massaro, An N. (American Journal of Perinatology, 2020)
Objective This study aimed to assess the association of clinical risk factors with severity of magnetic resonance imaging (MRI) brain injury in neonatal extracorporeal membrane oxygenation (ECMO) patients.Study Design This is a single-center retrospective study conducted at an outborn level IV neonatal intensive care unit in a free-standing academic children's hospital. Clinical and MRI data from neonates treated with ECMO between 2005 and 2015 were reviewed. MRI injury was graded by two radiologists according to a modified scoring system that assesses parenchymal injury, extra-axial hemorrhage, and cerebrospinal fluid spaces. MRI severity was classified as none (score = 0), mild/moderate (score = 1–13.5), and severe (score ≥ 14). The relationship between selected risk factors and MRI severity was assessed by Chi-square, analysis of variance, and Kruskal–Wallis tests where appropriate. Combinative predictive ability of significant risk factors was assessed by logistic regression analyses.Results MRI data were assessed in 81 neonates treated with ECMO. Veno-arterial (VA) patients had more severe injury compared with veno-venous patients. There was a trend toward less severe injury over time. After controlling for covariates, duration of ECMO remained significantly associated with brain injury, and the risk for severe injury was significantly increased in patients on ECMO beyond 210 hours.Conclusion Risk for brain injury is increased with VA ECMO and with longer duration of ECMO. Improvements in care may be leading to decreasing incidence of brain injury in neonatal ECMO patients.Key Points
Keywords: extracorporeal life support; neonate; magnetic resonance imaging; brain injury